2022
DOI: 10.1186/s12879-022-07100-3
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the congenital syphilis prevention cascade: qualitative findings from Kern County, California

Abstract: Background Congenital syphilis is preventable through timely access to prenatal care, syphilis screening and treatment of pregnant women diagnosed as infected. In 2018, California had the second highest number of congenital syphilis cases in the United States (U.S.), a nearly twofold increase in cases since 2014. This study assessed gaps in preventing congenital syphilis in the high morbidity region of Kern County, California. Methods Between May 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…This was followed by a lack of timely prenatal care in 28% and late identification of seroconversions in 11% [14]. Entry gaps to prenatal healthcare, retention gaps between prenatal visits, syphilis testing, and treatment appointments are obstacles to care, especially in at-risk populations struggling with poverty or substance use [16]. Persons who use substances of abuse during pregnancy may also avoid prenatal healthcare due to fear of judgment and legal consequences from healthcare providers, further increasing the risk of delayed diagnosis and missed or delayed treatment for this particularly vulnerable group [16].…”
Section: Epidemiological Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was followed by a lack of timely prenatal care in 28% and late identification of seroconversions in 11% [14]. Entry gaps to prenatal healthcare, retention gaps between prenatal visits, syphilis testing, and treatment appointments are obstacles to care, especially in at-risk populations struggling with poverty or substance use [16]. Persons who use substances of abuse during pregnancy may also avoid prenatal healthcare due to fear of judgment and legal consequences from healthcare providers, further increasing the risk of delayed diagnosis and missed or delayed treatment for this particularly vulnerable group [16].…”
Section: Epidemiological Trendsmentioning
confidence: 99%
“…Entry gaps to prenatal healthcare, retention gaps between prenatal visits, syphilis testing, and treatment appointments are obstacles to care, especially in at-risk populations struggling with poverty or substance use [16]. Persons who use substances of abuse during pregnancy may also avoid prenatal healthcare due to fear of judgment and legal consequences from healthcare providers, further increasing the risk of delayed diagnosis and missed or delayed treatment for this particularly vulnerable group [16]. Methamphetamine and heroin use have been identified as risk factors [1] for acquiring syphilis during pregnancy and may partially explain the high concentration of CS cases in the Southwestern US [17].…”
Section: Epidemiological Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two qualitative studies from the United States identified key socioeconomic barriers to accessing care such as stigma and shame around social vulnerabilities, lack of education, distrust of healthcare systems, substance abuse and inadequate provider training. Public health policies need to be tailored to address these issues [29 ▪ ,30].…”
Section: Testing In Pregnancymentioning
confidence: 99%
“…4 Gaps in prevention efforts relate to limited access to prenatal care, social and psychological barriers, cultural factors, substance use, and domestic or intimate partner violence. 8 Addressing these challenges requires implementing personalized public health interventions and healthcare strategies to control and eliminate syphilis infection. These interventions aim to bridge gaps, provide targeted interventions, and ensure comprehensive care to prevent and address the spread of syphilis.…”
Section: Introductionmentioning
confidence: 99%